Formulation of Flame-Retardant Waxes and Evaluation of Combustion Characteristics of Treated Wood Using Mass Loss Calorimetry - Hyung Woo Lee; Jae Hee Jung; Jong-Shin Lee; Soon Park; Seon-Mee Yoon (BioResources)
The objective of this study was to synthesize flame-retardant wax by nano-sizing a previously developed flame-retardant with favorable performance characteristics. Additionally, this study assessed the leaching resistance of wood treated with flame-retardant wax. The findings revealed that wood treated with flame-retardant wax demonstrated no notable change in the weight loss rate before and after weathering treatments. In contrast, wood treated exclusively with flame retardants exhibited a discernible increase in the extent of weight loss. Furthermore, the leached phosphorus content was measured during the weathering process, revealing that the amount extracted from wood treated with flame-retardant wax was approximately 1/20 times of that extracted from wood treated with flame-retardant agents. Therefore, that wood treated with flame-retardant wax demonstrated superior flame-retardant performance before and after weathering treatments.